Fatigue and recovery of neuromuscular function after a simulated soccer match - Thomas, K.; Dent, J.; Howatson, G.; Goodall, S. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
INTRODUCTION: Soccer match-play induces transient and on-going decrements in physical function that persist for up to 72 hours postgame (Nedelec et al., 2012; Minnet & Duffield, 2014). There are frequent congested periods in the competitive schedule that require multiple games per week, separated by as little as 48 hours. Consequently, understanding and managing fatigue and the associated recovery post-match is an important consideration. Previous work has characterised the recovery of peripheral function after a soccer match, but there is sparse data on the recovery of neuromuscular function (Rampinini et al., 2011). The aim of the study was to assess the fatigue and recovery of neuromuscular, physical and perceptual responses following a simulated soccer match. METHODS: Fifteen semiprofessional male soccer players completed a 90 min simulated soccer match. Pre-, immediately-post and at 24, 48 and 72 h participants completed a battery of tests. Maximum voluntary force (MVC) and twitch responses to femoral nerve stimulation during isometric knee-extensor contractions and at rest were measured to assess central (voluntary activation, VA) and peripheral (quadriceps potentiated twitch force, Qtw,pot) fatigue. Creatine kinase (CK) was analysed from capillary blood samples as a humoral index of muscle damage. Countermovement jump (CMJ), reactive strength index (RSI) and sprint performance (10 & 20 m) were assessed to profile the recovery of physical function, alongside perceptual markers of recovery (active & passive soreness, fatigue). RESULTS: Simulated soccer match play elicited decrements in MVC that remained unresolved at 72 h (P = 0.01). Qtw,pot declined by 13% post-match (P < 0.001) and remained depressed until 72 h post. VA was reduced by 8% post-match and remained below baseline at 72 h (P = 0.049). CK was elevated postmatch and remained elevated at 72 h post (P < 0.001). CMJ performance remained depressed at 72 h (P < 0.01), RSI was decreased at 48 h (P < 0.01) but recovered by 72 h, and sprint performance recovered by 24 h. Perceptual markers of fatigue were elevated until 48 h post (P < 0.01) and had recovered by 72 h. DISCUSSION: Simulated soccer match-play induced significant fatigue that was both central and peripheral in origin. The loss in maximal voluntary force was not restored by 72 h post-match, and was accompanied by persistent central fatigue. The similar time-course recovery of neuromuscular function, jump performance and perceptual markers of fatigue indicates these tools might be useful as indices of fatigue and recovery in soccer players.